Newborn Weight Loss During Birth Hospitalization and Breastfeeding Outcomes Through Age 1 Month. (February 2017) - Flaherman, Valerie J.; Schaefer, Eric W.; Kuzniewicz, Michael K.; Li, Sherian; Walsh, Eileen; Paul, Ian M.
Background: Weight loss is universal for exclusively breastfed newborns in the first few days after birth. Many newborns exclusively breastfed during birth hospitalization receive formula in the first month after discharge and thus cease exclusive breastfeeding. However, the relationship between early weight loss and subsequent cessation of breastfeeding and exclusive breastfeeding is unknown. Research aim: This study aimed to determine the relationship between newborn weight loss and duration and exclusivity of breastfeeding among newborns breastfed exclusively during the birth hospitalization. Methods: Retrospective cohort study at Kaiser Permanente Northern California hospitals between 2009 and 2013. The main predictor variable was weight loss during birth hospitalization. The main outcomes were cessation of breastfeeding and cessation of exclusive breastfeeding in the first 25 days after discharge. Results: Among our sample, 83, 344 were exclusively breastfed during birth hospitalization. At 25 days after discharge, 15.6%, 95% confidence interval (CI) [14.6%, 16.6%], of those delivered vaginally and 17.6%, 95% CI [14.5%, 20.6%], of those delivered by cesarean section were estimated to have completely ceased breastfeeding; 57.0%, 95% CI [55.5%, 58.4%], and 57.9%, 95% CI [53.6%, 61.8%], respectively, had ceased exclusive breastfeeding. Survival curves depicting rates of breastfeeding cessation through 1 month did not differ by degree of weight loss or by weight loss trajectory. However, curves depicting rates of exclusive breastfeeding demonstrated significantly more formula use among those with more weight loss at discharge. Conclusion: Among those exclusively breastfed during birth hospitalization, weight loss nomograms may help identify newborns at higher risk of cessation of exclusive breastfeeding. Lactation support targeted to those with exacerbated weight loss trajectories may improve duration of exclusive breastfeeding.